IMPLEMENTASI REHABILITASI TERHADAP ANAK SEBAGAI KORBAN PENYALAHGUNAAN NARKOTIKA - Andi Winarni (FAKULTAS HUKUM UM PAREPARE, 2019)
This study aims to determine the implementation of rehabilitation of children as victims of narcotics abuse. This type of research is empirical research. The results of this study indicate that the implementation of rehabilitation of children as victims of narcotics abuse so far not considered effective. This is because there is no separation conducted by BNN Baddoka Rehabilitation Center between adult resident and resident of child. So that the therapy program (rehabilitation) obtained by the child is no different from that obtained by adults. Factors that impede the implementation of rehabilitation of children as victims of narcotics abuse are (a) legal substance factors, in which there are no clear rules governing the form and type of rehabilitation given to victims of childhood narcotics abuse; (b) facilities and facilities factors. The absence of adequate human resources (HR) and facilities to carry out child-specific rehabilitation; (c) individual factors of the child, family and community. The presence of it wants to be free of children and fear of slanted news obtained by the child about the condition of the rehabilitation hall to make children and families became reluctant to bring their children to undergo rehabilitation program. Meanwhile, the negative stigma of the people about the victims of drug abuse has not changed. Those who have completed the rehabilitation program at the rehabilitation center are also viewed as dangerous negative figures if they exist in the community